Answer:
15
Step-by-step explanation:
Y = 2(x – 2)+1
y = 2x – 4+1
y = 2x-3
insert x=0 -> y=-3, only the first graph passes through (0,-3) -> it is the first graph
2) C: 4+d
3) A: x-3
4) C: 5(1-f)
I know that this is a few weeks late...
but hope this helps!
Luke earned $54 for 3 lawns
So each lawn = $54/3 = $18
After mowing 7 lawns =
7 X $18 = $126
The rule to use is PEMDAS. (Parenthesis, Exponents, Multiplication, Division, Addition, and Subtraction) When there's a number in front of one parenthesis, you distribute that number to the terms on the inside based on PEMDAS. What should also be notified is the exponent rules for multiplication and division. Then combine like terms. They have to have the same base of multiplying or dividing. Combining like terms need to have the same exponent, or whole numbers in groups.